Perceived effectiveness of drainage systems in Ybiernas St. Iloilo - Dela Fuente, Kathleen Marie G.; Dellava, Joy Cathyrine B.; Margacenio, Julienne N.; Orendez, Cliffy james D.; Pedrablanca, Regine E.; Salvador, Stephanie Dane S.
The study of drainage system in Iloilo City specifically along Ybiernas St. will bring major benefits. As the improvement of the drainage system, it reduces the damages to the houses and public facilities. Minimize the effects of flooding along Iloilo City, thus creating a great help both the residents and people that are affected by flooding of the area like college students, employees of establishments in the area and even passers-by. flooding is a perennial problem in Iloilo City, various flood and drainage system projects have been implemented in Metropolis in the past years, but it seems only a little have been gained because the flood problems will persist. Flood control and drainage system has yet effectively address due to the inadequate capacity of existing drainage channels in conveying storm water to the dumping stations. The drainage improvement measure has been hampered by the very limited information in the present conditions of existing drainage channels. A survey is done to test whether the respondent view their drainage system as effective in controlling flood when rain and storm occurs. The result of this research study would be of great help in evaluating whether the drainage system needs further improvement or it simply needs maintenance. First hand evaluation of people that are near or have experience in the place is very useful tool in the evaluation process of government projects.